DEBACER: a method for slicing moderated debates - Ferraz, Thomas Palmeira; Alcoforado, Alexandre; Bustos, Enzo; Oliveira, André Seidel; Gerber, Rodrigo; Müller, Naíde; d’Almeida, André Corrêa; Veloso, Bruno Miguel; Costa, Anna Helena Reali (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2021: Anais do XVIII Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2021.18293, 2021)
Subjects change frequently in moderated debates with several participants, such as in parliamentary sessions, electoral debates, and trials. Partitioning a debate into blocks with the same subject is essential for understanding. Often a moderator is responsible for defining when a new block begins so that the task of automatically partitioning a moderated debate can focus solely on the moderator's behavior. In this paper, we (i) propose a new algorithm, DEBACER, which partitions moderated debates; (ii) carry out a comparative study between conventional and BERTimbau pipelines; and (iii) validate DEBACER applying it to the minutes of the Assembly of the Republic of Portugal. Our results show the effectiveness of DEBACER.